If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5q-3q-q=15
We move all terms to the left:
5q-3q-q-(15)=0
We add all the numbers together, and all the variables
q-15=0
We move all terms containing q to the left, all other terms to the right
q=15
| 15x-3(4x+15)=15 | | 4u+14=2 | | 15=(x+1)5 | | 17a-13a-3a+3=10 | | -9i=-72 | | 3x+8x+9=49 | | 9=a/22 | | 5(4x-8)=3(2x+2) | | 4x2-130=-6x | | 3d+12=20+dd= | | 4*a/3=-24 | | 9=s/3= | | 16c+3c+c-18c-1=11 | | 18q-15q-3q+2q-2=4 | | 9=s/3=27 | | 45+125m=260 | | x÷4-15=-13 | | -12q-15=-13 | | 250-40x=30 | | 3(x+6)=4(×+5) | | 2x2=36+x | | 4÷x-15=-13 | | 2k+k+2k-k=20 | | 4y+16=(-32) | | 11v+4v-13v+1=17 | | -2x(x-2)+4x=-3(x+4)+13 | | 9y-5y+6y-8=12 | | 2x+9/4=9.5x | | -2y+16=0 | | 6z-13=z+12 | | 3/x+4-2/x-4=5x/x2-16 | | 2(z-3)=14 |